ChemInform Abstract: Gold‐Catalyzed Synthesis of 1‐Naphthylcarbenoids and Their Synthetic Utilization in Cyclopropanation Reactions. Issue 33 (19th August 2014) - Lauterbach, Tobias; Ganschow, Michael; Hussong, Matthias W.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract Transformation of norbornene under the investigated conditions suffers from incomplete conversion, but succeeds with gold (I) chloride as the catalyst.